Hubungan Dukungan Sosial Dengan Citra Diri Pada Pasien Ca Mamae Post Mastektomi Di Murni Teguh Memorial Hospital - Syafitri, Indah; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2024)
Mastectomy is one of the recommended surgical procedures for breast cancer patients. As a result of this action the patient will experience a disturbance in self-image. Social support is believed to be able to influence the occurrence of an increase in one's body image, because with the involvement or acceptance of the closest people it can help in the progress of one's re-integrity so that individuals can accept the physical changes that occur in themselves. The objective of this study is to identify the relationship between social support with self-image in patients with ca mamae post mastectomy at Murni Teguh Memorial Hospital. This study was conducted on 30 respondents using a descriptive correlative methodology with a cross-sectional approach and using simple random sampling technique. The instruments used social support and self-image questionnaire on post-mastectomy patients which have been tested for validity and reliability. Statistical test using Spearman correlation test. The results of this study indicate that there is a relationship between social support and self-image in post-mastectomy breast cancer patients at Murni Teguh Memorial Hospital Medan. Statistical test using Spearman correlation test showed p value <0.005 (p value = 0.002). It is concluded that there is a relationship between social support and self-image in post-mastectomy mammary patients at Murni Teguh Memorial Hospital Medan in 2022